"Am I Famous Yet?" Judging Scholarly Merit in Psychological Science: An Introduction. (November 2016) - Sternberg, Robert J.
The purpose of this symposium is to consider new ways of judging merit in academia, especially with respect to research in psychological science. First, I discuss the importance of merit-based evaluation and the purpose of this symposium. Next, I review some previous ideas about judging merit—especially creative merit—and I describe some of the main criteria used by institutions today for judging the quality of research in psychological science. Finally, I suggest a new criterion that institutions and individuals might use and draw some conclusions.